Turnover rate of metallothionein and cadmium in Mytilus edulis - Bebianno, Maria João (2020)
The results demonstrate the first attempt to determine metallothionein turnover in the whole soft tissues of mussels Mytilus edulis exposed to cadmium. Half-lives for metallothionein and cadmium are 25 and 300 days, respectively. As metallothionein degrades the released cadmium induces further synthesis of the protein, to which the metal becomes resequestered. The slow metallothionein turnover rates (compared with mammals) and the lack of significant cadmium excretion testify to the relatively stable nature of the cadmium-metallothionein complex in these invertebrates and supports the view of a detoxifying role for metallothionein in the mussels.